Chitosan improves the durability of resin-dentin interface with etch-and-rinse or self-etch adhesive systems - Vitória Leite PASCHOINI; Isabella Rodrigues ZIOTTI; Cláudio Roberto NERI; Silmara Aparecida Milori CORONA; Aline Evangelista SOUZA-GABRIEL (University of São Paulo, 2021)
Abstract Degradation of the dentin-resin interface can occur due to hydrolysis of exposed collagen, resulting in reduced bond strength. This study assessed the effect of dentin treatment with chitosan combined with an etch-and-rinse or self-etch adhesive system on improvement of bond strength and preservation of the interface durability. Methodology Enamel was removed from 80 molars and the teeth were divided into two groups: without chitosan (control) or with 2.5% chitosan gel (1 min). They were further subdivided into two subgroups according to the adhesive system: etch-and-rinse or self-etch. Dentin was restored using a composite resin. Half of the specimens from each restored group were subjected to interface aging and the remaining specimens were used for immediate analysis. The specimens were sectioned and subjected to microtensile bond strength (µTBS) test (n=10), chemical composition testing using Fourier-transform infrared (FTIR) spectroscopy (n=4) and energy-dispersive spectroscopy (EDS) (n=5), and morphological analysis of the adhesive interface using scanning electron microscopy (SEM) (n=5). Data were analyzed using three-way ANOVA. Results Chitosan improved the µTBS of the adhesive interface when compared with the control group (p=0.004). No significant differences were observed in dentin adhesion between the adhesive systems (p=0.652). Immediate µTBS was not significantly different from that after 6 months (p=0.274). EDS and SEM did not show significant differences in the chemical and structural composition of the specimens. FTIR showed a decrease in the intensity of phosphate and carbonate bands after using chitosan. Conclusions Dentin treatment with chitosan combined with an etch-and-rinse or self-etch adhesive system improved the immediate and preserved the 6-month bond strength of the adhesive interface.